2005
DOI: 10.1212/01.wnl.0000162054.15428.e9
|View full text |Cite
|
Sign up to set email alerts
|

Motor signs predict poor outcomes in Alzheimer disease

Abstract: Objective-To examine whether the presence of motor signs has predictive value for important outcomes in Alzheimer disease (AD). Methods-A total of 533 patients with AD at early stages (mean Folstein Mini-Mental StateExamination [MMSE] 21/30 at entry) were recruited and followed semiannually for up to 13.1 years (mean 3) in five University-based AD centers in the United States and European Union. Four outcomes, assessed every 6 months, were used in Cox models: cognitive endpoint (Columbia Mini-Mental State Exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
128
0
11

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(147 citation statements)
references
References 54 publications
8
128
0
11
Order By: Relevance
“…25,26,[36][37][38][39][40][41][42][43][44] Many studies have reported shorter survival for men with dementia as compared with women. 42, 45-48 Regarding ethnic differences, the literature is mixed, with some studies finding higher mortality for Caucasians with AD 26,49 and some others reporting no race differences.…”
Section: Discussionmentioning
confidence: 99%
“…25,26,[36][37][38][39][40][41][42][43][44] Many studies have reported shorter survival for men with dementia as compared with women. 42, 45-48 Regarding ethnic differences, the literature is mixed, with some studies finding higher mortality for Caucasians with AD 26,49 and some others reporting no race differences.…”
Section: Discussionmentioning
confidence: 99%
“…Among those are especially early signs of the motor system. They are predictors of fast decline as well as poor outcome (Mangone, 2004;Portet et al, 2009;Scarmeas et al, 2005). Another potential indicator / predictor of a rapid disease course might be the presence of psychotic symptoms (Wilkosz et al 2010).…”
Section: Clinical Signs Symptoms and Comorbidity As Predictors Of Famentioning
confidence: 99%
“…Presence of extrapyramidal symp toms in studies with AD patients has been found to increase with disease progression [6, 7], and to predict faster cognitive and functional decline, institutionalization, and eventually death [7, 8]. Different motor symptoms have been associated with different outcomes, and the presence and rating of motor symptoms have varied among studies.…”
Section: Introductionmentioning
confidence: 99%
“…Different motor symptoms have been associated with different outcomes, and the presence and rating of motor symptoms have varied among studies. Tremor, for instance, has been associated with increased risk of cognitive decline [8] while it in other studies has been found to be the least frequent motor sign to develop in AD patients [6-9]. In the heterogeneous group of FTD, parkinsonism has been reported in up to 20% of patients suffering from the behavioral variant FTD, less often in patients with the non-fluent variant primary progressive aphasia FTD, and in the semantic variant FTD [10].…”
Section: Introductionmentioning
confidence: 99%